The hidden potential of organisational planning: matching Alexander's theory of patterns to practice - Dickie, Carolyn; Forde, Patrick (Irish Academy of Management, 2007)
Generally, it is true of people that they will look for patterns and attach meaning to the patterns they find. Alexander et al. (1977) originally conceived the concept of pattern languages within the architecture community and since the early 1990s patterning has been used widely to document software development practices. Most uses of these patterning efforts have focussed on software from a technical aspect; however, authors such as Coplien & Harrison (2004) have moved beyond purely technical aspects and have used the concept of patterns to discuss issues of organization structure. As demand on managers and their time has increased substantially in recent times, streamlining and making traditional management processes more efficient and time effective has become an area of increasing concern. Management has become a hugely complex and demanding task on people. Further, there is a significant cost to the organization to ensure management staff are trained and capable in their role.The ability of managers to make good decisions in all aspects of management clearly affects the success of the organization as a whole. The volume of processes managers are expected to understand and involve themselves in, and the rate at which the environment and processes change, has led to the development of a variety of business process management tools. Most business process management tools are used to manage, track or simplify core processes by recognising patterns that can be replicated easily to produce more efficient management and more effective outcomes. However, there is limited research and development of process management tools for the traditional management processes of planning, leading, organizing and controlling.Despite the potential for improved understanding, training and practice of planning, there is a dearth of literature or practical resources developed on the concept of management patterns. Flexible patterns would allow simple comparison between the model and the actual situation, thus providing a direct link between theory and practice and facilitating easy change to the conceptual model or adjustment to the practice or both. The challenge for researchers in this relatively new area of study is to map and codify existing management processes, fill in the gaps in knowledge and bring the work to the attention of the business community, writers in the business community and business academics.The current study linked the management process of planning with Alexander et al.?s (1977) concept of patterns developed within architecture and later expanded to the information systems arena. The major focus of the study was to propose a model for identifying patterns in the management process of planning. The model was developed from responses received from managers as to the management planning process in ten organisational workplaces from a range of industries.Whether practitioners seek continuous improvement through controlling business inputs or processes, planning of outcomes is critical. Practical implementation difficulties continue despite a plethora of independent planning tools/applications. Using Alexander?s concept of ?patterning?, an underlying pattern that faithfully represents actual planning practices has been identified. Despite idiosyncracies in organisations, there are common themes that fit planning in public/private sectors alike; they can be used to improve dramatically the success of professional planning practices.